Computational Visualization and Informatics Interaction Analysis of Daidzein Compound from Soybean (Glycine max L.) on Maltase-Glucoamylase Protein for Predictive Study of Intestinal Disaccharidase Deficiency - Zainul, Rahadian; Elkhool, Tarek A.; Ahmed, Shafique; Goh, Khang Wen; Muhardi, - (Society of Visual Informatics, 2025)
This study explores the potential of daidzein, a bioactive compound derived from soybean (Glycine max L.), as a maltase-glucoamylase protein inhibitor to address intestinal disaccharidase deficiency, utilizing in silico methodologies. The research supports Sustainable Development Goal 3: Good Health and Well-being by evaluating the binding interactions, physicochemical properties, and therapeutic potential of daidzein. Structural data of daidzein and maltase-glucoamylase were analyzed using PyMOL, PyRx, Protein Plus, and Lipinski’s Rule of Five to predict interaction mechanisms and drug-likeness. The methodological framework consisted of molecular docking and physicochemical analysis, including binding affinity and Root Mean Square Deviation (RMSD) evaluations. The docking results demonstrated strong and stable interactions between daidzein and the target protein, with binding affinities of -2.5 and -2.4 kcal/mol. Additionally, key physicochemical parameters—such as molecular weight (254) and log P (2.713)—indicated favorable drug-likeness and oral bioavailability. RMSD values supported the stability of daidzein within the enzyme’s active site. These findings suggest that daidzein may serve as a promising natural therapeutic agent for digestive disorders associated with enzyme deficiencies. The study also illustrates the efficiency of computational tools in the early stages of drug discovery, reducing reliance on laboratory testing. It is recommended that future research includes in vitro validations and preclinical studies to further assess the safety, efficacy, and pharmacokinetics of daidzein. Structural optimization to enhance target binding is also encouraged. Ultimately, this research contributes to the sustainable development of plant-based therapies for managing non-communicable diseases and improving digestive health.